THE INFLUENCE OF SHEVCHENKO’S CREATIVE HERITAGE ON THE EDUCATION OF YOUTH THROUGH THE LANGUAGE AND LITERATURE FIELD OF EDUCATION - Войтенко, Г.М. (Modern engineering and innovative technologies, 2024)
The article examines the theoretical justification of the educational goal in the lessons/classes of the linguistic and literary field of education and the focus on T.G. Shevchenko’s work. Forms of value orientations of education seekers were studied. The